Comprehensive Performance Evaluation of Phase Change Materials Using Multi-Attribute Decision Making Method: TOPSIS (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract- Phase change materials store large amount of heat in the form of latent heat of fusion. For latent heat thermal energy storage systems, the comprehensive performance evaluation of phase change materials is very important task for the selection of the most suitable phase change material from among multiple alternative one. It is a typical multi-attribute decision making (MADM) problem. This work proposed a MADM approach to evaluate the comprehensive performance of the phase change materials using technique for order preference by similarity to ideal solution (TOPSIS), and applied it to evaluate the comprehensive performance of 9 alternative phase change materials for solar domestic hot water system. As the result, the comprehensive performance ranking of the phase change materials was n-eicosane, n-octadecane, n-nonadecane, RT 60, RT 30, calcium chloride hexa-hydrate, n-docosane, p116, and stearic acid. It could be actively applied to not only the phase change materials but also various materials comprehensive performance evaluation ones arising in practice.